THE ROLE OF RETURN ON EQUITY, DEBT TO EQUITY RATIO AND CURRENT RATIO IN REVEALING THE STOCK PRICES (THIS RESEARCH ON TELECOMMUNICATION SUB SECTOR COMPANIES WHICH HAVE BEEN LISTED ON THE INDONESIA STOCK EXCHANGE 2012-2019) - Fitri Rasdayanti; Chaerudin Chaerudin (Dinasti Publisher, 2021)
This research has purposes to discover and examine the impact which causing from return on equity (ROE), debt to equity ratio (DER) and current ratio (CR) against stock prices in sub-sector telecommunications companies which have been registered on the IDX during period of 2012 - 2019. This research currently uses a quantitative method with sampling technique used was purposive sampling technique during the research period so the samples used were EXCEL, FREN, ISAT and TLKM. The research data used was secondary data through multiple linear regression analysis method. The results had shown that 1) ROE had a positive and significant impact on stock prices; 2) DER had no impact on stock prices; 3) CR had a positive and significant impact on stock prices; and 4) ROE, DER, and CR had simultaneously impact on stock prices.